Analisis Sistem Informasi Union Catalogue Perpustakaan UIN Raden Fatah Palembang dengan Pendekatan EUCS - Rusmiatiningsih - (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2018)
The Library of UIN Raden Fatah Palembang is one of the university libraries that uses a system automation and union catalog system to meet the information needs of the academic community. This study aims to determine the level of satisfaction of users in utilizing union catalog using the End User Computing Catalog Satisfaction (EUCS) approach. This study uses a quantitative method with a total sample of 100 visitors to the Palembang Raden Fatah UIN Library. From the calculation of the mean and grand mean it was found that the subvariable content obtained a high score of 3.98, the subvariable accuracy obtained a high score of 3.97. In the subvariabel the format obtained a high score of 4.09. punctuality earned a high score of 4.01. The grand mean catalog satisfaction variable together with the End User Computing Satisfaction approach, obtained a value of 4.03 from the average value of 5 satisfaction subvariables. With a value of 4.01 which indicates that user satisfaction is at a high level. Keywords: author guidelines, Pustaka Budaya, article template